Hubungan Kebugaran Jasmani dan Motivasi Belajar terhadap Prestasi Belajar Siswa SD Negeri 2 Tanjung Jawa - Cilvia Liantini; Sumarjo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze and examine: (1) the relationship between physical fitness and learning achievement in Physical Education (PJOK) among students of SD Negeri 2 Tanjung Jawa, (2) the relationship between learning motivation and learning achievement in Physical Education (PJOK) among students of SD Negeri 2 Tanjung Jawa, and (3) the relationship between physical fitness and learning motivation simultaneously with learning achievement in Physical Education (PJOK) among students of SD Negeri 2 Tanjung Jawa. This study employed a quantitative approach using an experimental method. The research sample consisted of 24 students, including 11 male students and 13 female students, comprising all fourth- and fifth-grade students of SD Negeri 2 Tanjung Jawa who were actively enrolled in the even semester of the 2025/2026 academic year. The instrument used to measure physical fitness was the Indonesian Physical Fitness Test (TKJI) for ages 10–13 years. Learning motivation was measured using a questionnaire, while learning achievement was obtained from the Mid-Semester Assessment (PTS) report card scores for the Physical Education (PJOK) subject in the even semester of the 2025/2026 academic year. The data analysis techniques used were correlation analysis and multiple linear regression. The results showed that: (1) physical fitness partially has a significant and positive relationship with learning achievement in Physical Education (PJOK) among students of SD Negeri 2 Tanjung Jawa; (2) learning motivation partially has a significant and positive relationship with learning achievement in Physical Education (PJOK) among students of SD Negeri 2 Tanjung Jawa; and (3) physical fitness and learning motivation simultaneously have a significant relationship with learning achievement in Physical Education (PJOK) among students of SD Negeri 2 Tanjung Jawa. Therefore, it can be concluded that physical fitness and learning motivation are important factors that contribute to improving students’ learning achievement in Physical Education. Keywords: Physical Fitness, Learning Motivation, Learning Achievement